The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ani10050805
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fungal Feed Additives in Animals: A Review

Abstract: As probiotics, fungi enhance animal health and are suitable animal feed additives. In addition to brewing fungi, there are also edible and medicinal fungi. Common fungi utilized in feeding programs include Saccharomyces cerevisiae, Aspergillus oryzae, Pleurotus spp., Antrodia cinnamomea, and Cordyceps militaris. These fungi are rich in glucans, polysaccharides, polyphenols, triterpenes, ergosterol, adenosine, and laccases. These functional components play important roles in antioxidant, anti-inflammatory, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 92 publications
0
29
0
2
Order By: Relevance
“…The comprehensive enzymes in their products could stimulate the growth of microorganisms by converting macromolecular nutrients to available nutrients for microorganisms, which increase the nutrient digestibility of the substrate and produce a large quantity of VFA to decrease pH in the medium [ 39 , 49 ]. Alternatively, the inactivated microorganisms and medium also provide limited nutrients for microorganisms and then enhance the nutrient digestibility, as evidenced in other fungi [ 50 ]. Regardless of the pathway, the intention is to improve the diversity and function of microorganisms through AOAN supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive enzymes in their products could stimulate the growth of microorganisms by converting macromolecular nutrients to available nutrients for microorganisms, which increase the nutrient digestibility of the substrate and produce a large quantity of VFA to decrease pH in the medium [ 39 , 49 ]. Alternatively, the inactivated microorganisms and medium also provide limited nutrients for microorganisms and then enhance the nutrient digestibility, as evidenced in other fungi [ 50 ]. Regardless of the pathway, the intention is to improve the diversity and function of microorganisms through AOAN supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The phytate usually form a complex with fiber in the WB, and therefore cannot degrade by phytase addition [10]. In the other hand, as the report of Chuang et al [14], S. cerevisiae could mainly secret fiber-related enzymes, such as glucanase, mannanase, cellulase and xylanase, etc. Therefore, fermentation of S. cerevisiae can degrade fiber in WB, S. cerevisiae still cannot decrease the phytase content in WB.…”
Section: A C C E P T E D a R T I C L E Introductionmentioning
confidence: 97%
“…A. melanogenum , which is widespread in nature, is a fungus that can produce EPSs and secrete various extracellular enzymes. It is widely used in the food processing industry and is a component of animal feed [ 31 , 34 , 39 , 41 ]. Since A. flavus, C. tenuissimum, and P. oxalicum have been studied in honey bees, A. melanogenum would be a good animal probiotic but has not been investigated in honey bees.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that exopolysaccharides (EPSs) produced by Aureobasidium melanogenum promote anti-inflammatory and anti-tumor activities in mammals [ 36 , 37 ] as well as cholesterol metabolism [ 38 ]. This explains the use of this fungus in animal feed additives [ 39 ]. Furthermore, this fungus secretes numerous enzymes, including amylase, cellulase, proteinase, lipase, xylanase, mannanase, polygalacturonase, and transferases [ 32 , 33 , 34 , 40 ], which are used widely in the food processing industry [ 41 ].…”
Section: Introductionmentioning
confidence: 99%